Estimating the Glomerular Filtration Rate in Pediatric Patients With Neurogenic Bladder: A Comparison Between Creatinine- and Cystatin C-Equations - Menezes, Catarina (2023)
Background and objective Patients with neurogenic bladder (NB) are at a higher risk of developing chronic kidney disease (CKD). Due to their lower muscle mass, the estimated glomerular filtration rate (eGFR) based on creatinine (Cr) may be overestimated and delay the diagnosis of renal failure. This study compared eGFR calculated with different equations based on Cr and/or cystatin C (CysC) in children with NB, and the differences between patients with lower muscle mass (underdeveloped lower limbs) and those with independent gait (less muscle depletion). Methods We calculated the eGFR in pediatric patients with NB and CKD stages 1 and 2 by using the following equations: Chronic Kidney Disease in Children equation for serum creatinine (CKiD-Cr), CKiD-CysC, CKiD combined-Cr/CysC, Zappitelli-CysC, and Zappitelli combined-Cr/CysC. Results We evaluated a total of 47 patients, 74.5% with CKD stage 1, with a median age of 14.1 years. Of these participants, 59.6% had lipo/myelomeningocele. The CKiD-Cr and CysC-based equations led to significantly lower calculated eGFR ​​(p<0.05), specifically CKiD-CysC (p<0.001), Zappitelli-CysC (p<0.001), CKiD-Cr/CysC (p<0.001), and Zappitelli combined-Cr/CysC (p<0.05). When CKiD-CysC was used, 68% of the patients moved to a more advanced CKD stage. In patients without independent gait, with lower muscle mass (55.3%), the median eGFR calculated using the CKiD-Cr and CKiD combined-Cr/CysC equations was significantly higher (p<0.05). However, there were no differences between the two groups when using the other CysC-based equations. Conclusion In patients with NB and poor muscle mass, the CKiD-Cr equation may overestimate renal function. CysC-based equations seem more reliable in these patients, especially in those with greater muscular atrophy.